2020
DOI: 10.1073/pnas.2000466117
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of soluble guanylate cyclase exerts antiinflammatory actions in the liver through a VASP/NF-κB/NLRP3 inflammasome circuit

Abstract: Soluble guanylate cyclase (sGC) catalyzes the conversion of guanosine triphosphate into cyclic guanosine-3′,5′-monophosphate, a key second messenger in cell signaling and tissue homeostasis. It was recently demonstrated that sGC stimulation is associated with a marked antiinflammatory effect in the liver of mice with experimental nonalcoholic steatohepatitis (NASH). Here, we investigated the mechanisms underlying the antiinflammatory effect of the sGC stimulator praliciguat (PRL) in the liver. Therapeutic admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 32 publications
(44 reference statements)
2
23
0
Order By: Relevance
“…Furthermore, praliciguat exhibited anti-inflammatory and anti-fibrotic effects in a choline-deficient l -amino acid-defined HFD-induced NASH mouse model. Praliciguat can suppress hepatic levels in NLRP3 inflammasome components, including IL-1 β , NLRP3, caspase-1, and ASC, and exerts anti-inflammatory function in the liver via a vasodilator-stimulated phosphoprotein/NF-κB/NLRP3 circuit ( Flores-Costa et al, 2020 ). Praliciguat can also reduce levels of the active form of cleaved caspase-1 after NLRP3 inflammasome activation, independent of pannexin-1 activity.…”
Section: Pharmacological Agents Associated With Nlrp3 Inflammasome Su...mentioning
confidence: 99%
“…Furthermore, praliciguat exhibited anti-inflammatory and anti-fibrotic effects in a choline-deficient l -amino acid-defined HFD-induced NASH mouse model. Praliciguat can suppress hepatic levels in NLRP3 inflammasome components, including IL-1 β , NLRP3, caspase-1, and ASC, and exerts anti-inflammatory function in the liver via a vasodilator-stimulated phosphoprotein/NF-κB/NLRP3 circuit ( Flores-Costa et al, 2020 ). Praliciguat can also reduce levels of the active form of cleaved caspase-1 after NLRP3 inflammasome activation, independent of pannexin-1 activity.…”
Section: Pharmacological Agents Associated With Nlrp3 Inflammasome Su...mentioning
confidence: 99%
“…Suppression of NF-κB-mediated inflammatory response ameliorated the hind limb dysfunction of SCII rats [ 12 ]. A study shows that NF-κB-induced oligomerization of NLRP3 with ASC and pro-caspase 1 forms the NLPR3 inflammasome [ 13 ]. Upon stimuli to stress, the activated NLRP3 inflammasome cleaves pro-caspase 1 to the mature caspase-1 p20 and subsequently releases pro-inflammatory factors IL-1β as well as IL-18 [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A few researches have revealed that NF-κB p65 is an important signaling pathway in local inflammatory environment of heart, where it induces differentiation of Th17 cells ( Cheng et al, 2016 ; Sun et al, 2016 ). Another study has revealed that activated sGC inhibits the NF-κB p65 signaling pathway ( Flores-Costa et al, 2020 ). Consequently, we evaluated the effect of activated cardiac NF-κB p65 in myocarditis disease condition.…”
Section: Discussionmentioning
confidence: 99%